Comparative analysis of natalizumab versus fingolimod as second-line treatment in relapsing–remitting multiple sclerosis. (May 2018) - Lorscheider, Johannes; Benkert, Pascal; Lienert, Carmen; Hänni, Peter; Derfuss, Tobias; Kuhle, Jens; Kappos, Ludwig; Yaldizli, Özgür
Background: No randomized controlled trials have compared the efficacy of fingolimod or natalizumab as second-line treatment in patients with relapsing–remitting multiple sclerosis (RRMS). Objective: To compare clinical outcomes after escalation to fingolimod versus natalizumab in patients with clinically active RRMS. Methods: Using the registry of the Swiss Federation for Common Tasks of Health Insurances, we identified patients with RRMS and ≥1 relapse in the year before switching from interferon beta or glatiramer acetate to fingolimod or natalizumab. Propensity score matching was used to select patients with comparable baseline characteristics. Relapse and Expanded Disability Status Scale (EDSS) outcomes were compared in paired, pairwise-censored analyses. Results: Of the 547 included patients, 358 were matched (fingolimod, n  = 179; natalizumab, n  = 179). Median follow-up time was 1.8 years (interquartile range 0.9–2.9). Patients switching to natalizumab had a lower risk of relapses (incidence rate ratio 0.5, 95% confidence interval (CI) 0.3–0.8, p  = 0.001) and were more likely to experience EDSS improvement (hazard ratio (HR) 1.8, 95% CI 1.1–2.7, p  = 0.01) compared to fingolimod. We found no differences in the proportion of patients free from EDSS progression (HR 0.9, 95% CI 0.5–1.5, p  = 0.62). Conclusion: Natalizumab seems to be more effective in reducing relapse rate and improving disability compared with fingolimod.